Strategi Penguatan Nilai-Nilai Moderasi Beragama melalui Pendidikan Multikultural - Mikraj, Mikraj; Fazal, Khairil; Chaizir, Muhammad (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to analyze strategies for strengthening the values of religious moderation through a multicultural education approach. Religious moderation is viewed as a crucial effort to maintain social harmony within a pluralistic society, while multicultural education serves as an effective medium to systematically instill these values in students from an early age. This research employs a library research method with a descriptive qualitative approach. Data were collected through an extensive review of relevant literature, including books, peer-reviewed journals, educational policy documents, and reports from educational institutions. The findings reveal that the reinforcement of moderation values can be achieved through the integration of tolerance and diversity into the curriculum, strengthening the role of teachers as agents of change and facilitators of inclusion, and fostering a school culture that embraces differences. However, the implementation process faces several challenges, such as ideological resistance rooted in exclusive religious interpretations, structural limitations within the education system, and cultural resistance from communities. On the other hand, opportunities arise from supportive government policies, curriculum flexibility, active involvement of civil society, and the strategic use of technology to promote the values of religious moderation